The complete nucleotide sequence of the carbapenem resistance-conferring conjugative plasmid pLD209 from a Pseudomonas putida clinical strain reveals a chimeric design formed by modules derived from both environmental and clinical bacteria - Marchiaro, Patricia (2014)
The complete sequence of the carbapenem-resistance-conferring conjugative plasmid pLD209 from a Pseudomonas putida clinical strain is presented. pLD209 is formed by 3 well-defined regions: an adaptability module encompassing a Tn402-like class 1 integron of clinical origin containing blaVIM-2 and aacA4 gene cassettes, partitioning and transfer modules, and a replication module derived from plasmids of environmental bacteria. pLD209 is thus a mosaic of modules originating in both the clinical and environmental (nonclinical) microbiota